A Case Series Evaluation of a Pilot Group Cognitive Behavioural Treatment for Children With Asthma and Anxiety. Issue 1 (16th March 2017) - Sicouri, Gemma; Sharpe, Louise; Hudson, Jennifer L.; Dudeney, Joanne; Jaffe, Adam; Hunt, Caroline
Abstract : Anxiety disorders occur at an increased rate in children with asthma; however, there is only a small evidence base to support specific psychological treatments for these children. The current study evaluated the efficacy of a pilot cognitive behavioural treatment (CBT) group intervention for children with asthma and a comorbid anxiety disorder in a case series design. Five children (aged 8–11 years old) with asthma and a comorbid anxiety disorder and their mothers took part in eight 1-hour group treatment sessions. Primary outcomes measures were anxiety diagnosis and asthma-related quality of life. Secondary outcome measures were asthma symptom control and parent quality of life associated with caring for a child with asthma. Three of the participants no longer met diagnostic criteria for an anxiety disorder following treatment and three different participants reported a reliable improvement in asthma-related quality of life. Two participants reported a reliable improvement in asthma symptom control. Three mothers reported an improvement in caregiver quality of life. The findings provide preliminary proof of concept evidence for the efficacy of a CBT intervention for children with asthma and clinical anxiety.